Autoimmune antibody in encephalopathic patients: A pilot study - Attawit Charoensri (2022)
Objective: To investigate the specificity of the antibodies related to autoimmune encephalitis and to identify possible associated factors with the false-positive result. Materials and Methods: The present study was a prospective observational study, conducted at the Ramathibodi Hospital between June and December 2019. All patients, who had acute to subacute encephalopathy from any causes, were recruited to the study. Their serum or cerebrospinal fluid (CSF) were taken to analyze for autoimmune encephalitis assays and anti-thyroid antibodies. The authors did not interfere with the primary physicians on any management of the patients. Clinical and laboratory data were systematically reviewed and collected from medical records. The clinical outcome was evaluated one month after the onset. Results: Fifty-one patients were recruited. Only one patient had autoimmune encephalitis related to anti-CV2/CRMP5 antibody. Seventeen out of the remaining fifty patients had positive tests for anti-thyroid antibodies of which five had Hashimoto's thyroiditis and one of them did not have the document of thyroid status. Eleven remaining patients appeared to have false-positive test since their medical conditions were all clearly explained by other causes. Comparison of clinical and laboratory data between patients with false-positive test and patients with true negative test did not show any significant difference except the duration of the symptoms, which was significantly shorter in the false-positive group. Conclusion: False-positive anti-thyroid antibodies appear to be common in patients with acute encephalopathy. The occurrence of serum/CSF antibody in acute encephalopathy may be a true association, but it may not be the cause of encephalopathy. Therefore, the diagnosis of autoimmune encephalopathy based on anti-thyroid antibodies should be carefully made and excluded from all other possible causes.